1994
DOI: 10.1136/hrt.71.5.422
|View full text |Cite
|
Sign up to set email alerts
|

Can power spectral analysis of heart rate variability identify a high risk subgroup of congestive heart failure patients with excessive sympathetic activation? A pilot study before and after heart transplantation.

Abstract: Background and objectives-Autonomic dysfunction seems to be involved in the progression and prognosis of severe congestive heart failure. Parasympathetic activity can still be abnormal 4-8 weeks after haemodynamic improvement by heart transplantation. To identify patients in heart failure with a more pronounced neural derangement and to analyse the changes in sympathetic and parasympathetic activity soon after heart transplantation, spectral indices of heart rate variability were assessed in 30 patients in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
3
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 42 publications
4
79
3
5
Order By: Relevance
“…The authors suggest that HRV is superior to other prognostic factors, such as EF, pulmonary capillary pressure, cardiac index, and serum sodium. Mortara et al 149 , studying patients before and just after heart transplantation, found similar results.…”
Section: Autonomic Dysfunctionsupporting
confidence: 65%
See 2 more Smart Citations
“…The authors suggest that HRV is superior to other prognostic factors, such as EF, pulmonary capillary pressure, cardiac index, and serum sodium. Mortara et al 149 , studying patients before and just after heart transplantation, found similar results.…”
Section: Autonomic Dysfunctionsupporting
confidence: 65%
“…In patients with CHF, the HRV is greatly reduced, reflecting sympathetic hyperactivity and reduction of vagal activity, correlating with the severity of the disease [148][149][150] . Several authors found correlation between HRV, LVEF 148,150 , and also the plasmatic level of noradrenaline 149,151 . Kienzle et al 151 did not find correlation between HRV and EF or FC.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not demonstrated how well ΔHR reflects established measures of autonomic tone in HF, including HR variability,4 HR recovery,3 norepinephrine spillover,2 baroreflex sensitivity, or muscle sympathetic nerve activity 8. Further studies will be required to better define the pathophysiological correlates of ΔHR.…”
Section: Discussionmentioning
confidence: 86%
“…Measures of more advanced autonomic dysfunction are indicators of the severity of HF and adverse prognosis 2, 3, 4, 5, 6. They may include heart rate variability,4, 7 heart rate recovery,3 baroreflex sensitivity,5 measurement of norepinephrine spillover,2, 7 and muscle nerve sympathetic activity 8. However, the techniques needed to identify these are complex, and their application requires considerable infrastructure and time and are, therefore, not well suited for serial testing in clinical practice.…”
Section: Introductionmentioning
confidence: 99%